The Influences of Education on Aesthetic Emotions and Aesthetic Evaluation - Momeni, Seyed (fi=Turun yliopisto|en=University of Turku|, 2019)
The major goal of the current study was to investigate the influences of education on aesthetic emotions and aesthetic evaluation. Two groups of art and non-art students and graduates participated in the study by watching an artistic and poetic short film and completing a survey (AESTHEMOS). Parametric and non-parametric techniques were employed to compare two groups in terms of their emotional responses and aesthetic evaluation of an aesthetic object. Overall, and unexpectedly, non-art students and graduates reported experiencing higher aesthetic emotional levels than that of the art students/graduates. Likewise, the film was rated higher by non-art students and graduates compared to art students and graduates. In other word, non-art students/graduates reported that they experienced higher aesthetic emotional response to the film and liked the film more in comparison with the corresponding group of art students/graduates. Art students/graduates also answered an open-ended question and stated that art education had transformed the way they felt, saw, heard and evaluated aesthetic objects and the entire world. The study also strived to explain why non-art students/graduates compared with art students/graduates felt more aesthetic emotions while watching the poetic short film that was assumed to be an aesthetic object. To do so, two reasons were examined that may account for such a difference. It was argued that the professional expertise and the type of art education may hinder one to experience aesthetic emotions. Moreover, three approaches to art education including, traditional art education, arts integration education and aesthetic education, were discussed.